(untitled) (Al Insyirah International Scientific Conference on Health, 2021)
Hand grip strength has been widely used as a lead measure in geriatric conditions such as frailty. This condition tends to be experienced by the elderly due to nutritional factors. The aim of this study was to determine nutrition status toward hang grip strength. This study was observasional analytic by cross sectional approach. Data were collected on nutritional status and handgrip strength. 120 elderly were selected by cluster sampling. All Data were presented with describing proportions of categorical variables. The correlation of nutritional status toward handgrip strength were used by chi-square. This study showed that low handgrip strength was 43,3 %, at risk of malnutrition was 27,5%. There is a relationship between nutritional status and handgrip strength ( p=0.011; OR= 0,634; 95%CI 0,421-0,952).The factor associated with hand grip strength was nutritional status.